The Philosophy of A. W. H. Adkins Virtue and Goodness in Ancient Greece. - Boylan, Michael (Cambridge Scholars Publisher, 2022)
The fundamental issues that structure social and political philosophy revolve around the tensions between cooperative (ethical) values and competitive (self-interested) values. This book presents an in-depth examination of how society reacts to these as they move forward in the ancient Greek world. This model uses a methodology that is universal and can be applied to cultures at various historical epochs. The book advocates a ""bottom-up"" approach that employs a Wittgenstein-style methodology that is exactly detailed as it examines social usage as a sign of what is valued. These tensions are.